THE FEDERAL HIGHWAY POLICE IN THE CONTEXT OF POLICE APPROACHES (STOP AND FRISK) TO PEOPLE WITH DISABILITIES - Melo de Sousa, Francisco Elenilson; Dias Teixeira, Zenaide (Atâtôt - Interdisciplinary Journal of Human Rights (UEG), 2025)
The article investigates how the Federal Highway Police conducts police approaches (stop and frisk) to people with disabilities (PWDs), highlighting challenges and gaps in aligning these practices with human rights guidelines. The research addresses the problem of the lack of clear protocols and specific records on interactions with PWDs. Based on a qualitative approach grounded in Edgar Morin's theory of complexity, methods such as bibliographic review, document analysis, and data requests through the Access to Information Law were employed. The results indicated that, despite being subject to national and international norms for the protection of PWDs, the Federal Highway Police shows deficiencies in agent training and lacks specific mechanisms for recording and handling cases involving this group. Emblematic cases, such as that of Genivaldo de Jesus Santos, highlight institutional failures. The study concludes that the development of public policies and specific protocols to ensure humane approaches aligned with the fundamental rights of PWDs is urgent. Furthermore, it recommends conducting empirical studies to assess the effectiveness of these actions and the impact of specific training in reducing abuses.
Keywords: People with Disabilities; Stop and Frisk; Federal Highway Police